Pola Pengobatan pada Pasien Malaria di Rumah Sakit Umum Daerah (RSUD) Timika, Kabupaten Mimika: Treatment Patterns in Malaria Patients in Timika General Hospital - Christin Claritha Mote; Sabaniah Indjar Gama; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Malaria is a contagious disease caused by the parasite Plasmodium (class Sporozoa) which attacks red blood cells in the human body, malaria is very high in endemic areas, one of which is in Papua Province, especially in Mimika Regency. This study aims to determine the characteristics and treatment patterns in inpatient malaria patients at Timika Hospital, Mimika Regency in the January-December 2022 period. The method used in the study was a descriptive non-experimental study with retrospective data collection of 100 medical record data of hospitalized malaria patients who met the inclusion criteria. The results showed that the male sex was more dominant than women with a total of 53 people. At the most dominant age, namely the age of 12-25 years, malaria becomes dominant with 25 people. Then in the most dominant job, namely students, became the main target of malaria infection as many as 25 people. Falciparum (tropical) malaria became dominant because the most cases of falsiparum malaria in Papua were 52 people. DHP (Dihydroartemisinin-piperaquine) treatment as many as 94 people, and artesunate as many as 98 people. For drug administration, proper dosage, and time administration, all in accordance with the management of the Ministry of Health. Keywords: Treatment pattern, patient Characteristics Abstrak Malaria merupakan penyakit yang menular disebabkan oleh parasit Plasmodium (kelas Sporozoa) yang menyerang sel darah merah pada tubuh manusia, malaria sangat tinggi di daerah endemik salah satunya dipropinsi papua kususnya dikabupaten mimika. Penelitian ini bertujuan untuk mengetahui karakteristik dan pola pengobatan pada pasien malaria rawat inap RSUD Timika Kab.Mimika pada periode januari-desember 2022. Metode yang digunakan pada penelitian yaitu studi non eksperimental secara deskriptif dengan pengambilan data secara retrospektif terhadap 100 data rekam medik pasien malaria rawat inap yang memenuhi kriteria inklusi. Hasil penelitian menunjukan bahwa pada jenis kelamin laki-laki lebih dominan di banding perempuan dengan jumlah 53 orang. Pada usia yang paling dominan yaitu usia 12-25 tahun menjadi dominan terkena malaria degan jumlah 25 orang. Kemudin pada pekerjaan yang paling dominan yaitu Pelajar menjadi target utama terinfeksi malaria sebanyak 25 orang. Malaria falciparum (tropika) menjadi dominan karena kasus malaria falsiparum terbanyak dipapua sebanyak 52 orang. Pengobatan DHP (Dihydroartemisinin-piperaquine) sebanyak 94 orang, dan artesunat sebanyak 98 orang. Untuk pemberian obat, tepat dosis, dan pemberian waktu, semua sesuai dengan penatalaksaan depkes. Kata Kunci: Pola Pengobatan, Karakteristik Pasien